(untitled) (Polifonia, 2014)
ABSTRACT: In recent times a body of scholarship has built up showing how new technologies are linked to the construction of hybrid and cosmopolitan youth identities through digital literacy practices. It is important therefore to consider the transformative potential of these practices in academic settings. Reviewing recent literature on digital literacy practices and hybridity, this paper argues for the need to pay greater attention to the ways in which the distribution of cultural capital exercises an influence on the relationship between school and ‘out of school’ literacies. Examples of examination processes in Brazil and Australia are presented to identify how educational inequalities are likely to be reproduced despite the inclusion in examinations of questions focusing on digital literacy. The paper contributes to our understanding of the relationship between vernacular cultural and linguistic formations and formal schooling. KEYWORDS: New literacies, digital literacy, social inequality, migration, cosmopolitanism RESUMO: Nos últimos tempos, várias pesquisas têm mostrado como as novas tecnologias estão ligadas à construção de identidades juvenis híbridas e cosmopolitas, através de práticas de letramento digital. É importante, portanto, considerar o potencial transformador dessas práticas em meios acadêmicos. Apresentando uma revisão da literatura recente sobre as práticas de letramento digital e hibridismo, este trabalho defende a necessidade de se prestar maior atenção às formas pelas quais a distribuição de capital cultural exerce uma influência sobre a relação entre letramentos fora e dentro da escola e "fora da escola". Exemplos de sistemas de prova no Brasil e na Austrália são apresentados para identificar como as desigualdades educacionais são susceptíveis de ser reproduzidas, apesar da inclusão de exames de questões relativas a letramento digital. O trabalho contribui para a nossa compreensão da relação entre formações culturais e linguísticas vernáculas e escolaridade formal. PALAVRAS-CHAVES: Novos letramentos, letramento digital, desigualdade social, migração, cosmopolitismo